(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Terrorism which has been on the increase in recent years is of much concern to both Governments and the private sectors .This research aims at reflecting the contemporary trends in international terrorism, and suggesting the possibility of their application for the Ghanaian private sector. Game Theory, which in recent years has been increasingly used in researches and in creating anti-terrorism strategies is the method of presentation of this write-up. Game Theory is rationally used to examine this phenomenon, and with the aid of economic instruments offer new remedies.